Melhoria no sistema de controle da estação de tratamento de efluentes do rio ligeiro - Bassetto, Fernando Henrique (2014)
This paper presents the implantation of a supervisory system with a programmable logic controller (PLC) with the purpose of improve the Rio Ligeiro’s seawage treatment control. Was made possible through the supervisory system and other necessary equipments, keep up with the process parameters, on real time, like pH, level, input flow, etc. The Modbus-RTU communication protocol was used to make the communication among supervisory system, PLC and the frequency inverters. Therefore, was possible to automate the treatment steps which were manual.